PERANAN USHUL FIQH DALAM MEMBANGUN SISTEM KETATANEGARAAN DI INDONESIA - mardani, muhamad (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
Ushul fiqh, as a foundational science in understanding Islamic law, plays an important role in building the constitutional system in Indonesia, especially in the context of a country that recognizes religious and cultural pluralism. Basic concepts in ushul fiqh, such as maqasid al-shariah (the objectives of Islamic law) and maslahah (public welfare), provide guidance for the formulation of public policies that align with the principles of justice, benefit, and the common good. In the context of Indonesia, which has a Muslim majority, the application of ushul fiqh principles can be seen in efforts to develop national laws based on Islamic values while not disregarding the pluralism of society. One concrete example of applying ushul fiqh in the Indonesian constitutional system is in the formulation of the 1945 Constitution of the Republic of Indonesia (UUD 1945), which accommodates values of social justice and diversity. The principles of ushul fiqh also assist